Belarus Heat Tariff Reform and Social Impact Mitigation - Zhang, Fan; Hankinson, Denzel (Washington, DC: World Bank, 2015)
The government of the Republic of Belarus plans to increase district heating tariffs to cost recovery levels and gradually phase out subsidies, replacing them with social assistance programs. Residential district heating tariffs in Belarus are currently at roughly 10–21 percent of cost-recovery levels. District heating subsidies are highly regressive, add costs to business, and create significant fiscal risks and macroeconomic vulnerabilities.